Development of DC voltage control from wind turbines using proportions and integrals for three-phase grid-connected inverters - Arckarakit Chaithanakulwat (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This research article presents the method to control the DC voltage of the boost converter by using a proportional-integral (PI) controller. With AC voltage from a wind turbine generator, converting to DC voltage level by rectifier, this DC voltage controlled by PI controller is to control boost converter that sends DC links to the inverter which converting alternating current voltage to direct current voltage through three-phase load and to the grid-connected system. For switching the IGBTs in the inverter, the PWM signal, on the hysteresis current control, is controlled by the signal from the detected reference voltage based on the grid-connected system and the voltage from a wind turbine generator. The tests made the comparison of results from the simulation with the MATLAB/Simulink program and result from the hardware on the prototype. The power quality results, such as harmonic, power factor, are in acceptable ranges.